Effect of Cryopreserved Cord Blood Serum and Placental Extract on Cold-Wound Healing - Kovalev, Gennadiy A.; Vysekantsev, Igor P.; Ischenko, Irina O.; Abrafikova, Liliya G.; Olefirenko, Aleksey A.; Sandomirskiy, Boris P. (Problems of Cryobiology and Cryomedicine, 2015)
The dynamics of planimetric and microbiological indices of cold wounds during therapy with cryopreserved cord blood serum (CCBS) and placenta extract (PE) has been studied. Cold wounds were modelled in Sphinx using the cryodevice with8.0 mmapplicator, temperature of â€“195Â°C and 60 sec exposure. Injections were started on day 3 following cryodestruction intramuscularly each other day by 0.1 ml/kg of body mass (5 injections in general). On day 7 after CCBC or PE introduction the wound area decreased 2.8 or 1.9 times, correspondingly. Wound area in non-trated animals decreased only to day 9. On day 21 the wound area in animals with PE treatment was 3.3 times smaller, than in non-treated ones, and CCBC application resulted in full epithelization of wounds. Application of CCBC and PE contributed to elimination of microbes in wounds. Number of germs in wounds of rats which were treated with CCBC or PE decreased starting from 7th day of observation (3.4 or 1.9 fold, correspondingly). On day 21 the number of germs in wounds of rats treated with PE was 8.4 times less than in control, and in case of CCBC no patogenic microflora was present. Thus, an expressed stimulation effect of CCBC and PE on wound healing was shown. The presented results offer the prospect to include the CCMA into the wound treatment protocols. Probl Cryobiol Cryomed 2015; 25(1):57-66.